Inferior thyroid artery pseudoaneurysm following button battery ingestion in a 9-month-old infant: a rare vascular complication - Povananthiran, Sharmaine Marie; Sim, Christina Loo Poh; Rajaram, Gomalaadevee; Othman, Mohd Yusran Bin; Tamaddun, Hafatin Fairos; Bakin, Salinawati Binti; Shaker Al-Azawi, Abd Al-Rhman Hikmet (International Surgery Journal, 2025)
Button battery (BB) ingestion poses a significant pediatric surgical emergency, with increasing global incidence and serious morbidity in young children. Vascular complications, particularly involving the inferior thyroid artery, are extremely rare but potentially fatal. We report a case of a 9-month-old, with unwitnessed BB ingestion, presented with a history of hemoptysis and noisy breathing. Two weeks after the incident, the child developed complications of a right inferior thyroid artery pseudoaneurysm secondary to delayed diagnosis of esophageal BB impaction. The case was further complicated by bacteremia, esophageal stricture, and nutritional compromise, necessitating a multidisciplinary approach including endoscopic removal, endovascular embolization, jejunostomy, and eventual gastrostomy. This case highlights the importance of early recognition, vascular imaging, and structured follow-up in the management of severe BB ingestion.